Pitfalls in Morphologic Identification by Digital Microscopy: Atypical Chronic Lymphocytic Leukemia. (21st September 2018) - Gonzalez-Marques, William; Tavernier, Felix; Ahmed, Tahmeena; Senzel, Lisa
Abstract: Introduction: Literature suggests that large, morphologically atypical chronic lymphocytic leukemia (CLL) cells may correlate with more aggressive disease. We may think of atypical CLL as being FMC7 positive, but some cases have a typical immunophenotype and only the morphology is atypical. Automated digital microscopy imaging technology enables a faster and more objective classification of lymphocyte variants. However, this method is not without pitfalls. Method: Medical records of 10 patients with a CLL diagnosis and atypical morphologic features, initially seen at Stony Brook Medical Center between August 2016 and December 2017, were reviewed. Lymphocyte morphology was evaluated using archived blood films and automated digital microscopy. Cases with >10% and <55% prolymphocytes, lymphoplasmacytoid cells, and larger cells with irregular nuclear borders, indentations, or clefts were classified as having atypical CLL morphology. Morphologic findings were compared with immunophenotype, cytogenetics, and clinical features. Conclusions: Most of the cases reviewed showed at least one marker of aggressive disease such as CD38 expression, trisomy 12, 7p deletion, splenomegaly, unmutated IGHV, and Richter's transformation. All cases showed a typical immunophenotype (coexpression of CD5 and CD19, positive for CD23, and negative for FMC7 and CD10). Digital microscopy provides simultaneous display of multiple cells on a high-definition widescreen monitor, which results in a faster and more objective classification of lymphocyte variants. However, we observed that the software sometimes misclassifies these variants and may put them in the plasma cell, monocyte, myelocyte, or blast categories. Another potential pitfall is that many laboratories add a drop of albumin before glass slide preparation. While this practice decreases cell smudging, it may result in overcalling some of these atypical CLL cells as blasts. When a blood smear has atypical CLL cells, comparing the smear to prior smears on the same patient can help avoid misclassification.